Prognostic factors associated with femoral head and neck excision outcomes in 108 dogs. A retrospective study - Krystalli AΑ; Sideri AΙ; Kazakos, G; Papaefthymiou SΚ; Savvas, I; Anatolitou AΑ; Prassinos NΝ (Journal of the Hellenic Veterinary Medical Society, 2025)
Femoral head and neck excision (FHNE) is a simple and non-reversible surgical procedure in which the entire femoral head and part of the femoral neck are removed obliquely. This allows the formation of a functional pseudarthrosis providing pain relief for dogs suffering from severe hip-joint disease. However, the factors affecting surgery’s outcome are controversial. This study included 108 client-owned dogs. Every dog underwent a physical, orthopaedic, and radiological examination. Postoperatively, each dog owner answered a dog-mobility questionnaire. The association between quantitative variables and parameters was examined by statistical analysis. The results show that the final weight-bearing time of the limb is negatively affected by the chronicity of the disease, while age and body weight do not affect it. No positive correlation was found in regard to the limitation of activity, administration of analgesia, and performance of physical therapy. A dog’s age and body weight, postoperative activity restriction, physical therapy, and the administration of analgesics do not affect the outcome of FHNE. The disease’s chronicity and, consequently, muscle atrophy negatively affect the progress after surgery.